An effective approach to tackling complex health policy challenges. Using a clinical microsystems approach and rethinking codesign - Duggan, M.; Dunbar, J. A.; Morgan, M. A.; Mc Namara, K. P.; de Courten, M. P.; Calder, R. V. (Frontiers in Public Health, 2024)
That people with serious mental illness have poor physical health and face a significant life expectancy gap compared with the general population is well known. Despite considerable policy focus in some countries, the gap in life expectancy remains. Tackling complex and persistent health problems such as this requires a systems-based approach, recognising the complexity of interacting components and their effects on the problem and on each other and applying collaborative analysis, design and implementation by those with knowledge of and expertise in the problem and the context. This paper describes the methods used to develop the Australian Being Equally Well National Policy Roadmap for better physical health care and longer lives for people with severe mental illness. Whilst recognising that high rates of physical health comorbidities are caused by many factors including lifestyle, access to high-quality healthcare and medication side effects, the work was focused on what could be done within Australian primary care to improve the physical health of this cohort. A Clinical Microsystem Approach was applied to synthesise clinical evidence with professional and lived experience, and an innovative policy development process was established, creating trust across all system levels. Participants with different kinds of knowledge and experience worked in discrete groups according to their professional or expert role whilst also being supported to participate in an intensive cross-collaboration. The potential value of this methodology for tackling other complex problems in health policy is discussed.